Phase field simulations of thermal annealing for all-small molecule organic solar cells - Ameslon, Yasin; Ronsin, Olivier J.J.; Harreiß, Christina; Will, Johannes; Rechberger, Stefanie; Wu, Mingjian; Spiecker, Erdmann; Harting, Jens (Physical Chemistry Chemical Physics, 2024)
Interest in organic solar cells (OSCs) is constantly rising in the field of photovoltaic devices. The device performance relies on the bulk heterojunction (BHJ) nanomorphology, which develops during the drying process and additional post-treatment. This work investigates the effect of thermal annealing (TA) on the all-small molecule DRCN5T:PC71BM blend with phase field simulations. The objective is to determine the physical phenomena driving the evolution of the BHJ morphology for a better understanding of the post-treatment/morphology relationship. Phase-field simulation results are used to investigate the impact on the final BHJ morphology of the DRCN5T crystallization-related mechanisms, including nucleation, growth, crystal stability, impingement, grain coarsening, and Ostwald ripening, of the amorphous-amorphous phase separation (AAPS), and of diffusion limitations. The comparison of simulation results with experimental data shows that the morphological evolution of the BHJ under TA is dominated by dissolution of the smallest, unstable DRCN5T crystals and anisotropic growth of the largest crystals.
CRIS-Team Scopus Importer:2025-02-04